Місце норм адміністративного права в системі правових засад кадрового забезпечення Державної митної служби України - Колобиліна, О. О.; Kolobylina, O. O. (Європейські перспективи. - 2023. - № 4. - С. 226-232, 2023)
Запропоновано авторське визначення поняття адміністративно-правове регулювання. Охарактеризовано нормативно-правові акти різної юридичної сили, норми яких спрямовані на врегулювання кадрового забезпечення Державної митної служби України. Аргументовано, що в системі відповідних засад ключове місце відводиться нормам адміністративної галузі права.

It was found that administrative-legal regulation is a regulatory and ordering influence on social-legal relations in the field of public administration, as well as in the direction of ensuring the performance of state functions and the activities of its bodies and their officials, carried out with the help of the norms of the administrative branch of law. It is noted that the key importance in the mechanism of administrative and legal regulation is played by regulatory and legal acts, with the help of which the order, boundaries, and other features of the regulation of the corresponding system of public legal relations are established. It is emphasized that the system of legal foundations of personnel support of the State Customs Service consists of a large number of normative legal acts of different legal force. It has been established that in the system of regulatory and legal regulation of personnel support of the State Customs Service, the norms of various branches of law, in particular, labor and administrative, are harmoniously combined. At the same time, the analysis provided an opportunity to substantiate that in the system of legal foundations of personnel support of the State Customs Service of Ukraine, the key place belongs precisely to the norms of the administrative branch of law, because it is with the help of the latter: 1) the order of activity of personnel support subjects, their administrative legal status, tasks and functions; 2) the organizational and managerial peculiarities of the internal activity of the State Customs Service, its organizational and staffing structure, which directly affects personnel policy, are regulated; 3) the administrative and legal forms and methods of staffing of this department are outlined; 4) the administrative procedures of personnel support are disclosed; etc.

Предложено авторское определение понятия административно-правовое регулирование. Охарактеризованы нормативно-правовые акты разной юридической силы, нормы которых направлены на урегулирование кадрового обеспечения Государственной таможенной службы Украины. Аргументировано, что в системе соответствующих основ ключевое место отводится нормам административной отрасли права.
Keywords: адміністративно-правове регулювання; норми адміністративного права; кадрове забезпечення; Державна митна служба України; administrative and legal regulation; norms of administrative law; personnel support; State Customs Service of Ukraine; административно-правовое регулирование; нормы административного права; кадровое обеспечение; Государственная таможенная служба Украины